COGITOCENTRIC PSYCHOLOGY: A NEW APPROACH AS A POSSIBILITY FOR PSYCHIC ORGANIZATION - da Silva Ripardo, Emanuel; Diógenes Ripardo, Nicholas (Health and Society, 2025)
This study proposes a critical review of the foundations of psychoanalysis, replacing the traditional conception of the unconscious with the notion of Psychic Veiling, a phenomenon responsible for obscuring the affective experience due to excess cognition. It also introduces the concept of Cogitocentrism, understood as the domination of thought over experience, a condition that leads to the alienation of subjectivity. In order to broaden this understanding, the theory of Psyches is presented, understood as dynamic entities that operate between the Implicit Ego and the Explicit Ego, structuring the psyche as a living and continuous flow. Based on contemporary phenomenological and critical reflections, this work proposes paths for a psychology oriented towards the integration of feeling, thinking and existing, offering a renewed perspective on clinical and theoretical processes.